2016
DOI: 10.1080/03602532.2016.1239630
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: 4β-hydroxycholesterol as an emerging endogenous biomarker of hepatic CYP3A

Abstract: A key goal in the clinical development of a new molecular entity is to quickly identify whether it has the potential for drug-drug interactions. In particular, confirmation of in vitro data in the early stage of clinical development would facilitate the decision making and inform future clinical pharmacology study designs. Plasma 4β-hydroxycholesterol (4β-HC) is considered as an emerging endogenous biomarker for cytochrome P450 3A (CYP3A), one of the major drug metabolizing enzymes. Although there are increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 64 publications
1
54
0
Order By: Relevance
“…Multiple studies have evaluated cholesterol-based endogenous biomarkers of CYP3A activity in the presence of inducers or inhibitors in different patient cohorts. 21 However, very few evaluated the ability of 4β-OHC to characterize intrinsic CYP3A activities in patients with different diseases using a validated comparator. It has been shown that CYP450 activities are modulated by certain pathological conditions, especially when inflammation status is increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have evaluated cholesterol-based endogenous biomarkers of CYP3A activity in the presence of inducers or inhibitors in different patient cohorts. 21 However, very few evaluated the ability of 4β-OHC to characterize intrinsic CYP3A activities in patients with different diseases using a validated comparator. It has been shown that CYP450 activities are modulated by certain pathological conditions, especially when inflammation status is increased.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 However, only few studies have measured 4β-OHC in different populations (e.g., patients with HIV, epilepsy, or gallstones) as an indicator of basal CYP3A4 activity before the administration of an inducer or an inhibitor. 21 Therefore, the objectives of this study were (i) to validate the use of both plasma 4β-OHC concentrations and 4β-OHC ratio (the molar ratio of 4β-OHC to total cholesterol plasma concentrations) as an endogenous biomarker of CYP3A activity in healthy subjects and (ii) to evaluate its reliability as a marker of CYP3A activity in a cohort of patients with type 2 diabetes (T2D). Midazolam was administered and used as a reference to validate 4β-OHC concentrations and ratio as biomarkers of basal CYP3A activity in our control and T2D populations.…”
Section: Study Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both CYP3A4 and CYP3A5 mediate the cholesterol biotransformation to 4β-OHC. 17 In vitro metabolism of tolvaptan was faster using human liver microsomes with CYP3A5*1/*1 than with *1/*3 or *3/*3. 7 Our data indicate that tolvaptan is metabolized by CYP3A5 rather than CYP3A4 in human beings.…”
Section: Discussionmentioning
confidence: 94%
“…Plasma 4β-OHC as a non-P-glycoprotein activity marker has been utilized in a number of biomarker studies for predicting the pharmacokinetics of CYP3A probes and influences of CYP3A inducers. 17,18 Plasma 4β-OHC is also useful for the discrimination of patients with CYP3A5*3/*3. 13 Plasma 25-hydroxyvitamin D (25-OHD) is another promising biomarker of CYP3A activity.…”
Section: Introductionmentioning
confidence: 99%